Measurement of differential cross sections for Z bosons produced in association with charm jets in pp collisions at root s=13 TeV - Sirunyan, A. M. (2021)
Measurements are presented of differential cross sections for the production of Z bosons in association with at least one jet initiated by a charm quark in pp collisions at root s = 13 TeV. The data recorded by the CMS experiment at the LHC correspond to an integrated luminosity of 35.9 fb(-1). The final states contain a pair of electrons or muons that are the decay products of a Z boson, and a jet consistent with being initiated by a charm quark produced in the hard interaction. Differential cross sections as a function of the transverse momentum p(T) of the Z boson and p(T) of the charm jet are compared with predictions from Monte Carlo event generators. The inclusive production cross section 405.4 +/- 5.6 (stat) +/- 24.3 (exp) +/- 3.7 (theo) pb, is measured in a fiducial region requiring both leptons to have pseudorapidity |eta| < 2.4 and p(T)> 10 GeV, at least one lepton with p(T)> 26 GeV, and a mass of the pair in the range 71-111 GeV, while the charm jet is required to have p(T)> 30 GeV and |eta| < 2.4. These are the first measurements of these cross sections in proton-proton collisions at 13 TeV.